Perceived organizational support and its relationship with organizational citizenship behavior / Mohd Fazil Jamaludin ... [et al.] - Jamaludin, Mohd Fazil; Zainal, Nurdiyana Nazihah; Adzahar, Khairul Azfar; Saharan, Mohd Shafiz; Zulazlan, Nur Syafiqah (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2018)
The objective of this study is to identify the relationship between perceived organizational support and organizational citizenship behavior. The arising problems in the organization relate to perceived organizational support, has captured the interest of many researchers to study the relationship between individuals and organizations. Questionnaires were distributed to 300 respondents among administration staff of government agency. The result from the data analysis found that there is a positive and significant relationship between perceived organizational support and organizational citizenship behavior. Using the Cronbach alpha, the reliability levels were at 0.733 and 0.929, respectively. In addition, the multiple regression analysis showed that perceived organizational support (β=0.124, p<0.05) significantly influences the organizational citizenship behavior. Therefore, employees who feel that they are well supported by their organization tend to perform better than those employees who have a low level of perceived organizational support. It can be concluded that perceived organizational support does have a relationship with organizational citizenship behavior